Efficiency of neurometabolic therapy among the patients with ischemic hemispheric stroke in recovery period - Kozyolkin, O. A.; Medvedkova, S. O.; Kuznietsov, A. A.; Козьолкін, Олександр Анатолійович; Мєдвєдкова, Світлана Олександрівна; Кузнєцов, Антон Анатолійович; Козёлкин, А. А.; Медведкова, С. А.; Кузнецов, А. А. (My University, 2019)
Cerebrovascular diseases, and especially their acute forms, cerebral strokes, are an important problem in modern medicine. The search and usage of new and more effective drugs, which contribute to the improvement of treatment results in the recovery period of the disease, are relevant. The aim of the study – to improve the treatment of patients with cerebral ischemic stroke in the recovery period by using phenylpiracetam in the complex therapy. Materials and Methods. The work presents the results of treatment of 70 patients (average age is (58.8±0.9) years) in the recovery period of ischemic hemispheric stroke (IHS). All the patients were divided into two clinical groups of 35 patients. The group 1 included the patients who received phenylpiracetam in a complex therapy orally in a daily dose of 200 mg, divided into 2 intakes: in the morning and at lunch for 30 days; the group 2 consisted of patients who received piracetam as a nootropic drug parenterally in a daily dose of 3000 mg once in the morning during 30 days. All the patients were carried out in the dynamics before the treatment and after 30 days the assessment of the state according to the stroke scale of the National Institute of Health in order to determine the severity of the stroke. The degree of functional restoration according to Modified Rankin Scale and the estimation of the ability of household skills and self-service according to the Barthel Index were determined. A dynamic evaluation of cognitive impairments was performed using the Mini-Menthal State Examination and the 10-word memory test. Results and Discussion. As a result of treatment, positive dynamics of all clinical-neurological and cognitive indicators was observed, it was more revealed in patients of the main group using phenylpiracetam, compared with the control group (p<0.05). In the main group, after the therapy, MMSE points increased by 13.0 % (p˂0.01) due to the improvement of most cognitive domains: memory in 2 times (p˂0.01), attention and calculation – by 33.3 % (p˂0.01), orientation – by 12.5 % (p˂0.01). In the control group it was registered statistically significant but less revealed, in comparison with the main group, the increasing of points according to MMSE (Δ% + 4.2 %, p˂0.01). Conclusions. The conducted research informs us about positive effects of the phenylpiracetam drug, which contribute to the improvement of treatment outcome among the patients with IHS in the recovery period.

Цереброваскулярные заболевания, особенно их острые формы, мозговые инсульты, являются важной проблемой в современной медицины. Поиск и применение новых и более эффективных препаратов, способствующих улучшению результатов лечения в восстановительный период заболевания, являются актуальными. Цель исследования – улучшить лечение больных ишемическим мозговым инсультом в восстановительном периоде путем применения в комплексной терапии препарата “Фенилпирацетам”. Материалы и методы. В исследовании представлены результаты лечения 70 больных (средний возраст (58,8±0,9) года) в восстановительном периоде ишемического полушарного инсульта (ИПИ). Всех пациентов разделили на две клинические группы по 35 лиц. Первую группу составили больные, которые в комплексной терапии получали препарат “Фенилпирацетам” перорально в суточной дозе 200 мг, разделенной на 2 приема, – утром и в обед в течение 30 дней, а вторую – больные, которые в качестве ноотропного препарата получали “Пирацетам” парентерально в суточной дозе 3000 мг однократно утром в течение 30 дней. Всем больным в динамике до лечения и через 30 дней проводили оценку состояния по шкале инсульта Национального института здоровья для определения степени его тяжести, особенно функционального восстановления по модифицированной шкале Рэнкина и оценку возможности бытовых навыков и самообслуживания по индексу Бартела. Оценивали динамичность когнитивных нарушений с использованием Mini–Menthal State Examination и теста запоминания 10 слов. Результаты исследований и их обсуждение. В результате проведенного исследования отмечали положительную динамику всех клинико-неврологических и когнитивных показателей, достоверно более выраженой она была у больных основной группы, где применяли препарат “Фенилпирацетам”, по сравнению с группой контроля (р<0,05). В основной группе после проведенной терапии зарегистрировано увеличение баллов по MMSE на 13,0 % (p<0,01) за счет улучшения большинства когнитивных доменов: памяти – в 2 раза (р<0,01), внимания и счета – на 33,3 % (р<0,01), ориентации – на 12,5 % (р<0,01). В контрольной группе зарегистрировано статистически значимое, но менее выраженное, по сравнению с основной группой, увеличение баллов по MMSE (Δ%+4,2 %, p<0,01). Выводы. Проведенное исследование свидетельствует о положительных эффектах препарата “Фенилпирацетам”, способствующие улучшению результатов лечения больных ишемическим полушарным инсультом в восстановительном периоде.

Цереброваскулярні захворювання, особливо їх гострі форми, мозкові інсульти, є важливою проблемою у сучасній медицині. Пошук та застосування нових і більш ефективних препаратів, що сприяють поліпшенню результатів лікування у відновний період захворювання, є актуальними. Мета дослідження – покращити лікування хворих на ішемічний мозковий інсульт у відновному періоді шляхом застосування в комплексній терапії препарату “Фенілпірацетам”. Матеріали і методи. У дослідженні представлено результати лікування 70 хворих (середній вік (58,8±0,9) року) у відновному періоді ішемічного півкульового інсульту (ІПІ). Усіх пацієнтів поділили на дві клінічні групи по 35 осіб. Першу групу склали хворі, які в комплексній терапії отримували препарат“Фенілпірацетам” перорально в добовій дозі 200 мг, яку розділили на 2 прийоми, – вранці та в обід упродовж 30 днів, а другу – пацієнти, яким в якості ноотропного препарату отримували “Пірацетам” парентерально в добовій дозі 3000 мг одноразово вранці протягом 30 днів. Усім хворим в динаміці до лікування і через 30 днів проводили оцінку стану за шкалою інсульту Національного інституту здоров’я для визначення ступеня його тяжкості, зокрема функціонального відновлення за модифікованою шкалою Ренкіна й оцінку можливості побутових навичок і самообслуговування за індексом Бартела. Оцінювали динаміку когнітивних порушень із використанням Mini–Menthal State Examination та тесту запам’ятовування 10 слів. Результати досліджень та їх обговорення. У результаті проведеного дослідження відзначали позитивну динаміку всіх клініко-неврологічних і когнітивних показників, вірогідно більш вираженою вона була у хворих основної групи, де застосовували препарат “Фенілпірацетам”, порівняно з групою контролю (р<0,05). В основній групі після проведеної терапії зареєстровано збільшення балів за MMSE на 13,0 % (p<0,01) за рахунок поліпшення більшості когнітивних доменів: пам’яті – в 2 рази (р<0,01), уваги та рахунку – на 33,3 % (р<0,01), орієнтації – на 12,5 % (р<0,01). У контрольній групі зареєстровано статистично значуще, але менш виражене, порівняно з основною групою, збільшення балів за MMSE (Δ %+4,2 %, p<0,01). Висновки. Проведене дослідження свідчить про позитивні ефекти препарату “Фенілпірацетам”, що сприяють поліпшенню результатів лікування хворих на ішемічний півкульовий інсульт у відновному періоді.
Ефективність нейрометаболічної терапії у хворих на ішемічний півкульовий інсульт у відновному періоді
Эффективность нейрометаболической терапии у больных ишемическим полушарным инсультом в восстановительном периоде
Keywords: stroke; recovery period; rehabilitation; інсульт; відновний період; реабілітація; инсульт; восстановительный период; реабилитация